"We Had to Stick Together": Black Boys, the Urban Neighborhood Context, and Educational Aspirations. Issue 1 (1st June 2019) - Brooms, Derrick
Abstract : Studies investigating disadvantaged urban neighborhoods often focus on students' academic underperformance, ways they succumb to environmental stressors, involvement in illicit activities, and adherence to street-oriented behaviors and culture. This article focuses on the ways a select group of Black boys in the US successfully navigated structural impediments and interpersonal challenges during their secondary school years and eventually matriculated to college. Drawing on interview data, the article examines students' sense-making and the importance of their peers in navigating the urban environment: (1) interactions with people in the neighborhood and (2) strategies to negotiate the urban environment context in pursuit of their educational aspirations. The students' narratives highlight the benefits they assign to their peer relationships and collectivist efforts to support their educational goals.